Plant quantity and quality regulate the diversity of arthropod communities in a semi‐arid grassland - Lu, Xiaoming; Zhao, Xuezhen; Tachibana, Taiki; Uchida, Kei; Sasaki, Takehiro; Bai, Yongfei; Koricheva, Julia (Functional ecology, 2021)
The quantity (e.g. biomass production) and quality (e.g. leaf nutrient content) of plants can strongly influence arthropod diversity, but few studies have tried to disentangle such effects. In this study, we examined the independent effects of plant productivity and leaf traits on the taxon richness and abundance of entire arthropod communities and multiple arthropod orders in replicated monocultures of 15 herbaceous species in the Inner Mongolian grassland. Total taxon richness of arthropod communities increased with plant productivity and an increase in a high nutrient content indicator (PC1) of plant leaf traits (e.g. high leaf nitrogen, phosphorus and water contents), but decreased with an increase in a poor nutrient content indicator (PC2) of plant leaf traits (e.g. high leaf lignin content but low SLA). Total abundance of arthropod communities increased with increasing plant productivity but decreased with increasing PC2. Many common, rather than rare arthropod orders, exhibited strong responses to the changes in plant quantity or quality. Taxon richness of Diptera, Neuroptera and Coleoptera responded positively to the increase in plant productivity and PC1, while taxon richness of Hemiptera and Coleoptera responded negatively to the increase in PC2. Abundances of Diptera and Coleoptera responded positively to the increased plant productivity, whereas abundances of Hymenoptera and Hemiptera responded negatively to the increased PC2. The order‐specific responses of arthropod richness and abundance to plant quantity or quality reflected the different food requirements and feeding behaviours of arthropods. Our findings demonstrate that plant quantity and quality can independently control richness and abundance of arthropod communities. The changes in plant productivity and nutrient content of different plant species may alter arthropod diversity and community structure, and these changes in turn may have strong cascading effects on multiple functions (e.g. prey, decomposers, pollinators and predators) in terrestrial ecosystems. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.